Supporting experts to develop experts: identifying critical components of mental simulations as a tool for teacher professional learning - Walsh, Marguerite E.; Matsumura, Lindsay Clare; Schunn, Christian D.; Zook-Howell, Dena (Frontiers in Education, 2025)
Adaptive expertise is central to teachers’ ability to facilitate ambitious, “student-centered” instruction in K-12 classrooms. Teachers are supported to develop adaptive expertise when they are provided opportunities to build their pedagogical knowledge and reasoning skills in authentic, “practice-based” professional learning contexts. In this article, we illustrate in depth how one empirically supported routine, Mental Simulations for Teacher Reflection (MSTR), can facilitate this learning in a video-based instructional coaching context. Using case study analytic techniques, we specifically identify the finer-grain subcomponents involved in an expert-facilitated MSTR routine and show how they are orchestrated using an illustrative vignette of a post-lesson reflective coaching conversation. We also provide a detailed description of the theoretical and empirical foundations of MSTR as a routine for developing adaptive teaching expertise. By elucidating and unpacking the detailed processes that underlie robust enactment of MSTR, we contribute insights that can help advance more consistent and high-quality teacher learning in similar kinds of reflection-based learning contexts.